Pengaruh Literasi Keuangan, Gaya Hidup, dan Penggunaan E-Wallet terhadap Manajemen Keuangan Pribadi pada Mahasiswa Pendidikan Akuntansi, Fakultas Ekonomi dan Bisnis - Arbangatun Indah Rejeki; Rizqi Ilyasa Aghni (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze: (1) the effect of financial literacy on personal financial management; (2) the influence of lifestyle on personal financial management; (3) the effect of e-wallet usage on personal financial management; and (4) the simultaneous influence of financial literacy, lifestyle, and e-wallet usage on personal financial management among Accounting Education students at the Faculty of Economics and Business, Yogyakarta State University. This research employed a quantitative approach with a causal associative design. The population consisted of students from the Accounting Education program, cohorts 2021–2023, with a sample of 173 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using descriptive statistics and multiple linear regression after fulfilling classical assumption tests. The results indicate that financial literacy has a positive effect on personal financial management with a contribution of 23%, while lifestyle and e-wallet usage have negative effects with contributions of 21% and 8%, respectively. Simultaneously, these three variables explain 46.4% of the variance in personal financial management, while the remaining 53.6% is influenced by other factors not examined in this study. Furthermore, the majority of respondents (88%) are categorized as having a high level of personal financial management based on interval classification analysis. It should be noted that preliminary findings showed an average score of 52% for personal financial management, which reflects a percentage-based mean score and differs from the categorical analysis used in the main study. Therefore, the difference does not indicate inconsistency but rather a variation in measurement approaches.